Coronary Artery Thrombosis: Is High Serum Homocysteine Level a Culprit? - Dubey, Laxman; Guruprasad, Sogunuru; Bhattacharya, Rabindra; Subramanyam, Gangapatnam (Nepalese Heart Journal, 2014)
Hyperhomocysteinemia is a risk factor of coronary artery disease associated to arterial thrombosis. We report a case in which coronary angiography showed full of thrombus causing total obstruction of the left anterior descending artery. Patient was managed successfully with intravenous thrombolysis. Biochemical analysis revealed a high serum homocysteine level. DOI: http://dx.doi.org/10.3126/njh.v11i1.10982 Nepalese Heart Journal 2014;11(1): 49-52